If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1(5x + 1) = -4x + 7 Reorder the terms: 2 + -1(1 + 5x) = -4x + 7 2 + (1 * -1 + 5x * -1) = -4x + 7 2 + (-1 + -5x) = -4x + 7 Combine like terms: 2 + -1 = 1 1 + -5x = -4x + 7 Reorder the terms: 1 + -5x = 7 + -4x Solving 1 + -5x = 7 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 1 + -5x + 4x = 7 + -4x + 4x Combine like terms: -5x + 4x = -1x 1 + -1x = 7 + -4x + 4x Combine like terms: -4x + 4x = 0 1 + -1x = 7 + 0 1 + -1x = 7 Add '-1' to each side of the equation. 1 + -1 + -1x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 7 + -1 -1x = 7 + -1 Combine like terms: 7 + -1 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6
| 3x+9x=360 | | (3x-2y)squared= | | 5m+3=2-4m | | 4x+23=x+20 | | 3/5x-9 | | 180=40x-21 | | 5x-35=-10 | | =(3x^3) | | 26x+20-6x^2=0 | | ((-2w^2)/u)^3 | | 26=1.1R+0.2R | | g(0)=-1/2 | | -8=3+s | | 0.6x+8.9=5.6 | | 6(y-8)+3=33 | | 18d+4d^2=10 | | -5(-6y+3)-7y=7(y-4)-1 | | 2w+46=-2(w-3) | | -1/2-3.5 | | 3a-16a+16=0 | | (4v-6)(5-V)=0 | | c^2-13c-30=0 | | 40=2L+2(8) | | y=-0.2x+4.2 | | 7amx-7c=4x+5y | | 38.76+e=227.5 | | 8y^3-6y-1=0 | | 4-(2-x)=-3(2x+6) | | 8y-(3-6y)=0 | | 4-3x=12x+9 | | x-.18=163.43 | | 7-4.3=8.5 |